A flexible printed non-enzymatic glucose sensor based on CeO2-doped ZnO nanostructures for plant applications - Joubert, Trudi-Heleen (University of Pretoria, 2026)
Dissertation (MEng (Electronic Engineering))--University of Pretoria, 2025.